Nutritional Defciencies and Their Behavioral Risk Factors in Alcohol Withdrawal Patients in Mongolia - Buddorj, Purevjargal; Davaasuren, Oyunsuren; Galsanjav, Otgon; Luvsandorj, Erdenebayar; Zuunnast, Khishigsuren (Central Asian Journal of Medical Sciences, 2019)
Objectives: This study aims to determine some nutritional and vitamin deficiencies, and to define some dietary factors affecting alcohol withdrawal patients. Methods: Data were collected from patients with alcohol withdrawal delirium admitted to 3 addiction care clinics in Ulaanbaatar. A total of 162 subjects were selected randomly with a ratio 1:1 to this case-control study. Nutrient intake was determined by questioning the patients regarding their food intake during the 24 hours prior to admission. Results: In patients with alcohol withdrawal delirium 13 nutrients from food were significantly lower. Two risk behaviors had weak and moderate effects leading to a statistically significant decrease in 11 nutrients. The risk of deficiency of fat and tryptophan intake was 17.54-22 times in drinking while hungry. Refusing food while drinking had a moderate effect in decreasing 9 nutrients by more than 57.8% in alcohol withdrawal patients. Conclusion: The level of 13 nutrients and vitamins from food were lower in patients with alcohol withdrawal delirium (p<.001). The dietary risk behaviors related to drinking were defined that lead to decreased fat, zinc, vitamin B12, tryptophan, and cysteine from their diet.